The tonoplast intrinsic aquaporin (TIP) subfamily of Eucalyptus grandis: Characterization of EgTIP2, a root-specific and osmotic stress-responsive gene - Rodrigues, Marcela I. [UNESP]; Bravo, Juliana P. [UNESP]; Sassaki, Flávio T. [UNESP]; Severino, Fábio E. [UNESP]; Maia, Ivan de Godoy [UNESP] (Elsevier, 2013)
Aquaporins have important roles in various physiological processes in plants, including growth, development and adaptation to stress. In this study, a gene encoding a root-specific tonoplast intrinsic aquaporin (TIP) from Eucalyptus grandis (named EgTIP2) was investigated. The root-specific expression of EgTIP2 was validated over a panel of five eucalyptus organ/tissues. In eucalyptus roots, EgTIP2 expression was significantly induced by osmotic stress imposed by PEG treatment. Histochemical analysis of transgenic tobacco lines (Nicotiana tabacum SR1) harboring an EgTIP2 promoter:GUS reporter cassette revealed major GUS staining in the vasculature and in root tips. Consistent with its osmotic-stress inducible expression in eucalyptus, EgTIP2 promoter activity was up-regulated by mannitol treatment, but was down-regulated by abscisic acid. Taken together, these results suggest that EgTIP2 might be involved in eucalyptus response to drought. Additional searches in the eucalyptus genome revealed the presence of four additional putative TIP coding genes, which could be individually assigned to the classical TIP1-5 groups. © 2013 Elsevier B.V.
Keywords: Abiotic stress; Aquaporin; Eucalyptus; Promoter; TIP; Tissue-specificity